An Analysis of the Challenges to Achieving Sustainable Practices in Nigeria's Construction Sector - Hyginus Unegbu; Danjuma YAWAS; Bashar Dan-asabe; Abdulmumin Akoredeley Alabi (Advances in Civil Engineering and Sustainable Architecture, 2025)
This study investigates the key barriers to the adoption of sustainable construction practices in Nigeria, focusing on regulatory, organizational, social, cultural, and technological factors. Utilizing a mixed-methods approach, the research combines qualitative case studies and interviews with quantitative survey data to identify these challenges. The findings highlight the multifaceted and interconnected nature of these barriers, with regulatory challenges—such as outdated building codes, insufficient legislative support, and bureaucratic inefficiencies—emerging as the most significant. Social and cultural resistance to change, coupled with limited public awareness of sustainable construction benefits, further complicate adoption. Technological challenges, including high costs of green materials and a shortage of skilled professionals, are also key obstacles. The study suggests that Nigeria can draw valuable lessons from other developing countries, such as South Africa, India, and Indonesia, where similar challenges have been addressed through proactive policies and innovative practices. Recommendations for overcoming these barriers include modernizing building codes, strengthening leadership in sustainability within the construction sector, and launching comprehensive public education campaigns to shift societal attitudes. The study further advocates for increased investment in green technologies and the development of local supply chains to reduce costs and enhance the accessibility of sustainable construction materials. By adopting these strategies, Nigeria can promote sustainable building practices and contribute to global knowledge on overcoming barriers to sustainability in developing economies.